CSF α-synuclein correlates with CSF neurogranin in late-life depression. (3rd April 2021) - Bruno, Davide; Reichert Plaska, Chelsea; Clark, Daniel P. A.; Zetterberg, Henrik; Blennow, Kaj; Verbeek, Marcel M.; Pomara, Nunzio
Abstract: Purpose/aim of the study: Major depressive disorder (MDD) in late life is linked to increased risk of subsequent dementia, but it is still unclear exactly what pathophysiological mechanisms underpin this link. A potential mechanism related to elevated risk of dementia in MDD is increased levels of α-synuclein (α-Syn), a protein found in presynaptic neuronal terminals. Materials and methods: In this study, we examined cerebrospinal fluid (CSF) levels of α-Syn in conjunction with biomarkers of neurodegeneration (amyloid-β 42, total and phospho tau) and synaptic dysfunction (neurogranin), and measures of memory ability, in 27 cognitively intact older individuals with MDD and 19 controls. Results: Our results show that CSF α-Syn levels did not significantly differ across depressed and control participants, but α-Syn was directly associated with neurogranin levels, and indirectly linked to poorer memory ability. Conclusions: All in all, we found that α-Syn may be implicated in the association between late life MDD and synaptic dysfunction, although further research is needed to confirm these results.